Pengaruh Penggunaan Model Problem Based Learning (PBL) dalam Pembelajaran Tematik Muatan PKn Terhadap Hasil Belajar Kognitif dan Afektif Siswa Kelas VI SDN 33 Rejang Lebong - Feri Irawan; Puspa Djuwita; Agus Susanta (Jurnal Kajian Pendidikan Dasar, 2024)
This study aims to determine the effect of using the problem based learning (PBL) model in Civics thematic learning on the cognitive and affective learning outcomes of class VI students at SD N 33 Rejang Lebong. This research uses quantitative research methods. The analysis technique used is analysis prerequisite test which includes normality, homogeneity test, variance, and hypothesis testing using the t test. The sample of this research was 25 students with a population of 41 students. Data collection is in the form of objective tests with multiple choices and questionnaires. Data from the inferential analysis of paired samples T-Test with the help of SPSS. The results of the study showed that the pretest average value was 56% and the posttest was 82%, so that it increased by 26%, while the control class using conventional learning obtained an average pretest value of 54% and posttest by 63%, so that the increase was 9%. So it can be concluded that the use of the Problem Based Learning model has an effect on the cognitive and affective learning outcomes of class VI students at SDN 147 Rejang Lebong.